Abolition feminisms - Bierria, Alisa; Caruthers, Jakeya; Lober, Brooke; Spade, Dean (Haymarket Books)
"Abolition Feminisms offers wide-ranging feminist abolitionist methods for liberation forged in collectivity, radical care, and transformation."--